Evaluation of the outcome after tendon transfer surgery for reanimation of the thumb after nerve injury of the upper limb - Youssif Ahmed Youssif Khachaba; Ahmed Gamil Elsharkawi; Ashraf Nehad Moharram; Hatem Mahmoud Helmy (Cairo : Youssif Ahmed Youssif Khachaba, 2012)
Peripheral nerve injuries in the upper limb have a high incidence rate, and lead to a profound negative effect on the thumb function that contributes with 40% of the overall hand function. Tendon transfer surgery is an important method for thumb reanimation in selected cases of injuries of median, ulnar and radial nerves, to restore function and balance to the hand
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of General Surgery
Issued also as CD
Keywords: Plastic surgery; Tendon transfer; Thumb reanimation